The Black feminist spatial imagination and an intersectional environmental justice - Ducre, Kishi Animashaun (Environmental Sociology, 2018)
Starting with seminal work from Katherine McKittrick and Katherine McKittrick and the late Clyde Woods, this paper compares and contrasts articulations of justice as espoused by Black feminism, ecofeminism, and the movement for environmental justice. The utilization of an intersectional genealogical approach allows for examination of the ways in which these movements might serve as the ideological bases for a Black feminist spatial imagination and an intersectional environmental justice. A Black feminist spatial imagination is an orientation that accounts for the merger of frames around race, gender, and ecology; it serves as a unique departure from conventional Black feminist analysis by its particular attention to the construct of space in Black feminist epistemology. Analysis reveals that manifestos engage similar strategies around boundedness, an identification among a collective identity and the subject of reproductive justice and liberation as wresting control and self-determination of physical bodies. The final task is an outline of essential tenets for a singular notion of justice of a Black feminist spatial imagination which incorporates the spirit of all of three manifestos and expands current environmental justice discourse to include those ‘who know no one knows’ while highlighting Black women’s agency in environmentally degraded environments. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: afro-féminisme; amériques; approches et analyses; corps; environnement; féminismes noirs; intersectionnalité; justice environnementale; justice reproductive; projet charge mentale; régions géographiques; thématiques; écoféminisme; états-unis

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge philosophy companions, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."--The publisher.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap